Renal dysfunction due to advance pelvic organ prolapse - Lubna Razzak; Saulat, Sherjeel (Journal of the Pakistan Medical Association, 2021)
Uterovaginal prolapse is the downward descent of the pelvic organ, resulting in protrusion of the vagina, uterus, bladder or rectum. The association between POP and hydronephrosis has been shown by various studies, but severe hydronephrosis leads to renal dysfunction are rarely seen. We report a case of 70 years old female with massive vaginal prolapse and chronic renal impairement. She presented with urinary tract infection (UTI) and raised creatinine levels of 4.5mg/dl. After correction of UTI, she surgically managed to relieve her obstructive symptoms. After surgery her creatinine levels drop to 2.0mg/dl but chronic renal failure persisted. Advance stage prolapsed may damage renal function if left untreated. Timely diagnosis and management may prevent irreversible damage to kidneys Continuous...